Feasibility study of entrepreneurship development in major parts of economic activity in rural areas (Case study: Central District of Boyer-Ahmad County) - mohamad Eskandary; Ahmad Taghdisi; Yousof GHanbari (تحقیقات کاربردی علوم جغرافیایی)
Entrepreneurship can have many positive effects in rural communities on the one hand, they face economic problems, especially in the areas of employment, poverty and lack of income and On the other hand, they have high environmental capabilities. This research is based on information collected through documentary and survey methods and Aiming to enable the development of entrepreneurship in major sectors of economic activity It has been done in the villages of the central District of Boyer-Ahmad County. The results showed that despite the motivation for progress, hard work and high risk-taking of employees in major sectors of economic activity (Agriculture, Industry and Services), The general situation of their entrepreneurial variables with an average of 2.618, At 99% confidence level, it is below average. The results showed the feasibility of the sub-sectors of economic activity Four economic subsectors of medicinal plants, Aquaculture, mineral water resources and tourism, respectively by average 3.548, 3.691, 3.705 and 3.419, They have high potential for entrepreneurship development. Also showed the results of Pearson test The degree of correlation between independent variables (Production of medicinal plants, aquaculture, mineral water resources and tourism) and Research dependent variable (entrepreneurship), Has been positive and statistically significant Respectively with 0.519, 0.179, 0.398 and 0.533 values.